Spawn (1992): origins collection, volume 15 ebook - holguin, Brian (Spawn (1992), 2018)
Angels and demons are making deals... and Spawn wants no part of it! He embarks on his own mission of vengeance against the scum of the city, punishing and purging doers of evil - old and young alike! Written by Brian Holguin with artist Greg Capullo providing legendary pencil work, Spawn: Origins Volume 15 collects classic issues of Spawn #87-92.. Author: Brian Holguin. Illustrator: Todd McFarlane, Greg Capullo . 2012 Todd McFarlane Productions, Inc..